Reputation and right to information: the communication of Samarco mining company in the case of Mariana (Minas Gerais, Brazil) environmental disaster - Alves, Mariana Carareto [UNESP]; Andrelo, Roseane [UNESP]; Cabral, Raquel [UNESP] (Univ Malaga, Inst Investigacion Relaciones Publicas, 2016)
The present article aims to analyze whether the intention of an organization, when informing their actions during a crisis, is merely work for its image and reputation or a manner of guaranteeing the right to information to society. To this end, with the assumption that information is a fundamental element to every citizen, and when any risky situation brings consequences and impacts to society, the right to information must be guaranteed. Taking that premise into account, this study gives thoughts on the ways in which mining company Samarco communicated with the Brazilian population on the Internet, after the failure of the tailing dam in the city of Mariana (Minas Gerais, Brazil) in 2015. In this regard, the contents available on the company's institutional website were analyzed and some aspects of the reputation strategies and the importance of the right to information to society during the fallout of a crisis were identified.
Keywords: Information; rights; environmental disaster; Samarco; reputation